DESIGN STRATEGY OF FOOTBALL STADIUM WITH GREEN ARCHITECTURE APPROACH IN SRAGEN REGENCY - Erpan Nur Saputro; Widi Suroto; Sri Yuliani (Universitas Sebelas Maret Surakarta, 2019)
In determining the design strategy football stadium that has a large scale requires some management that can provide design strategy of football stadium. this large-scale stadium will have an impact on energy, water, sewage, land and comfort and surrounding environment also impacts of. Therefore this football stadium sould be minimize the negative impact on the environment, the application of green architecture was chosen. So the application of the green architecture concept to the football stadium in Sragen district aims to support the green city development program in Sragen regency. The research method that is used is the initial idea of exploration method, searching data and processing data. Design strategy of football stadium in Sragen district with green architecture approach is by using of solar panel as a renewable energy source. The application off windows in football stadium will be provided in some spaces. The implementation of community paths are pedestrian paths, bicycle lanes, access lines for the disabled and motor vehicles. The application of green land amounts about 40% of the total available land and the application of membrane material to provide natural light.